Effect of Non Surgical Periodontal Therapy on Gingival Crevicular Fluid and Serum Visfatin Concentration in Periodontal Health and Disease. Issue 6 (21st May 2013) - Raghavendra, N.M.; Pradeep, A.R.; Kathariya, Rahul; Sharma, Anuj; Rao, Nishanth S.; Naik, Savitha B.
Abstract : Visfatin is a pleiotropic mediator which acts as growth factor, cytokine, enzyme involved in energy including nicotinamide adenine dinucleotide metabolism and has been recently demonstrated to exert several pro-inflammatory functions. The purpose of this study is to evaluate the Visfatin concentration in gingival crevicular fluid (GCF) and serum in patients with chronic periodontitis, and to evaluate the effect of non-surgical periodontal therapy on the GCF and serum visfatin concentration. 30 subjects (age range: 25 to 52 years) were selected and divided into two groups based on the gingival index, probing depth, periodontal attachment level, and radiologic parameters (bone loss): group 1 (15 subjects with healthy periodontium), group 2 (15 subjects with chronic periodontitis), while, Group 2 patients after 8 weeks of the treatment (scaling and root planning, SRP) constituted group 3. GCF samples (by microcapillary pipettes) and serum samples (by venipuncture) were collected to estimate the levels of Visfatin using enzyme linked immunosorbent assay kit. The mean Visfatin concentration in GCF and serum was observed to be the highest in group 2 and lowest in group 1. While concentration in group 3 was similar to group 1. The concentration of Visfatin in GCF and serum decreased after SRP. The Visfatin concentration in GCF and serum found to be highest in chronic periodontitis group and decreases after treatment. Hence Visfatin values can be considered as an "inflammatory marker" can be explored in future as a potential therapeutic target in the treatment of periodontal disease.